Victory, 1918 - Palmer, Alan 1926- (1998)
When an armistice was finally signed in the forest of Compiegne outside of Paris, the Great War had shuddered to an end, but not before it had been fought on three continents, three oceans, and nine seas. Studies of World War I tend to focus on the Western front, the muddy trenches of France and Belgium, which is particularly problematic considering the final year of the conflict, when offensives in the Balkans, the Middle East, Italy, and the West all ended with decisive victories for the Allied powers. Alan Palmer embraces the full scope of the war and illuminates many of the major players -- Allied generals Sir Douglas Haig, Sir Edmund Allenby, Ferdinand Foch, and John J. Pershing; Central Powers generals Paul von Hindenburg and Erich Ludendorff; as well as David Lloyd George, Britain's prime minister. Victory 1918 is rife with tales of horrible misunderstandings such as the Austrian emperor Charles's appeal for peace on September 14, 1918, which was thought by the Allies to be a trick and, if taken seriously, could have saved as many as a quarter of a million lives. As he ably shifts between the diplomatic big picture and the local horrors of the trenches, Palmer presents the war in all its banality and valor.